1973
DOI: 10.7326/0003-4819-79-3-368
|View full text |Cite
|
Sign up to set email alerts
|

Microangiopathic Hemolytic Anemia in Metastatic Carcinoma

Abstract: Fig 3.-Section of thymoma removed at surgery (hematoxylineosin, x40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
6

Year Published

1983
1983
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(42 citation statements)
references
References 22 publications
0
35
1
6
Order By: Relevance
“…1 patient was in need of dialysis due to progressive renal failure, whereas the 2nd patient showed symptoms of HUS (microangiopathic changes in blood smear, thrombocytopenia, and elevation of creatinine < 3.0 × ULN) but without clinical consequences. Microangio- [25][26][27][28]. It could be shown that cumulative doses of MMC up to 200 mg can be given without any occurrence of HUS events [18].…”
Section: Discussionmentioning
confidence: 99%
“…1 patient was in need of dialysis due to progressive renal failure, whereas the 2nd patient showed symptoms of HUS (microangiopathic changes in blood smear, thrombocytopenia, and elevation of creatinine < 3.0 × ULN) but without clinical consequences. Microangio- [25][26][27][28]. It could be shown that cumulative doses of MMC up to 200 mg can be given without any occurrence of HUS events [18].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer patients microangiopathic hemolytic anemia (MAHA) is usually seen in advanced disease [1,2]. Hemolytic uremic syndrome (HUS) is a special form of MAHA with predominantly renal involvement.…”
Section: Introductionmentioning
confidence: 99%
“…In a review article of HUS, Gold stein et al [12] mentioned such an association referring to the study of Lohrman et al [13] in which metastatic carcinoma was associated with MAHA but not HUS. Among previous observations of HUS in association with malignancy we found only 3 reports where the syn drome occurred in the absence of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%